Germline determinants of humoral immune response to HPV-16 protect against oropharyngeal cancer - Ferreiro-Iglesias, Aida; McKay, James D; Brenner, Nicole; Virani, Shama; Lesseur, Corina; Gaborieau, Valerie; Ness, Andy R; Hung, Rayjean J; Liu, Geoffrey; Diergaarde, Brenda; Olshan, Andrew F; Hayes, Neil; et al. (Nature communications, 2021)
Although several oropharyngeal cancer (OPC) susceptibility loci have been identified, most previous studies lacked detailed information on human papillomavirus (HPV) status. We conduct a genome-wide analysis by HPV16 serology status in 4,002 oral cancer cases (OPC and oral cavity cancer (OCC)) and 5,256 controls. We detect four susceptibility loci pointing to a distinct genetic predisposition by HPV status. Our most notable finding in the HLA region, that is now confirmed to be specific of HPV(+)OPC risk, reveal two independent loci with strong protective effects, one refining the previously reported HLA class II haplotype association. Antibody levels against HPV16 viral proteins strongly implicate the protective HLA variants as major determinants of humoral response against L1 capsid protein or E6 oncoprotein suggesting a natural immune response against HPV(+)OPC promoted by HLA variants. This indicates that therapeutic vaccines that target E6 and attenuate viral response after established HPV infections might protect against HPV(+)OPC.
Keywords: exprese genu; Gene Expression; Meta-Analysis as Topic; represorové proteiny; Mouth Neoplasms; haplotypy; Male; Genetic Predisposition to Disease; protilátky virové; Risk Factors; onkogenní proteiny virové; infekce papilomavirem; Papillomavirus Infections; metaanalýza jako téma; Haplotypes; Genome-Wide Association Study; Aged; Case-Control Studies; mužské pohlaví; senioři; Capsid Proteins; HLA antigeny; nádory orofaryngu; Human papillomavirus 16; virové plášťové proteiny; Smoking; lokus kvantitativního znaku; lidský papilomavirus 16; lidé; ženské pohlaví; studie případů a kontrol; humorální imunita; Humans; Oropharyngeal Neoplasms; Quantitative Trait Loci; rizikové faktory; HLA Antigens; Repressor Proteins; Antibodies, Viral; Female; nádory úst; Immunity, Humoral; lidé středního věku; Oncogene Proteins, Viral; kouření; genetická predispozice k nemoci; celogenomová asociační studie; Middle Aged